2022
DOI: 10.3390/buildings12081229
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Maintenance 4.0 for Chilled Water System at Commercial Buildings: A Systematic Literature Review

Abstract: Predictive maintenance plays an important role in managing commercial buildings. This article provides a systematic review of the literature on predictive maintenance applications of chilled water systems that are in line with Industry 4.0/Quality 4.0. The review is based on answering two research questions about understanding the mechanism of identifying the system’s faults during its operation and exploring the methods that were used to predict these faults. The research gaps are explained in this article an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 196 publications
0
7
0
Order By: Relevance
“…Almobarek et al [9] performed a systematic review of the literature on predictive maintenance applications of chilled water systems (CWS) and focused on two aspects: (1) the identification of operational faults and (2) the methods to better predict them. The authors covered chillers, cooling towers, circulating pumps, and terminal units and pinpointed the lack of studies tackling the entire CWS (rather than focusing on specific components); they also suggested that more attention should be given to cooling towers and pumps.…”
Section: The Papersmentioning
confidence: 99%
See 2 more Smart Citations
“…Almobarek et al [9] performed a systematic review of the literature on predictive maintenance applications of chilled water systems (CWS) and focused on two aspects: (1) the identification of operational faults and (2) the methods to better predict them. The authors covered chillers, cooling towers, circulating pumps, and terminal units and pinpointed the lack of studies tackling the entire CWS (rather than focusing on specific components); they also suggested that more attention should be given to cooling towers and pumps.…”
Section: The Papersmentioning
confidence: 99%
“…Almobarek et al [10] conducted an industry survey to complement the aforementioned systematic review outputs [9]. This survey targets the identification and frequencies of more operational faults and fault solutions for chilled water systems.…”
Section: The Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous initiatives have tackled similar topics, but the focus was rather on specific applications: metadata schemas [18], data analytics [19], FDD [20], model-based predictive controls (MPC) [9,[21][22][23], reinforcement learning [24], occupant-centric controls (OCC) [25,26], predictive maintenance [27], peak load management [28], building energy flexibility [29], strategies for building energy management systems (including MPC, demand side management, optimization, and FDD) [8], and data-driven building operations (with a focus on metadata, FDD, OCC, key performance indicators, virtual energy meters, and load disaggregation) [30]. Some other work emphasized the perspectives, challenges, and opportunities but also concentrated on specific aspects: industry engagement [31], data requirements for MPC [32], reinforcement learning [33], and OCC [34].…”
Section: Paper Objectivementioning
confidence: 99%
“…However, the great majority of deep learning and machine learning systems for identifying control automation do not provide more detailed information about the patterns and their turning points (even when these patterns are seen on control charts). This information is required to undertake a realistic analysis of assignable causes, which in turn expedites the execution of suitable remedial measures [ 8 , 9 ]. To help quality control staff members locate the origins of deviations and take the appropriate preventative or corrective measures, this study aims to suggest the development of a defect detection system that utilizes hybrid convolutional neural networks.…”
Section: Introductionmentioning
confidence: 99%